Biogeography and ecology of the genus Turbinicarpus (Cactaceae): environmental controls of taxa richness and morphology. Issue 4 (4th July 2017) - Donati, Davide; Bianchi, Claudia; Pezzi, Giovanna; Conte, Lucia; Hofer, Anton; Chiarucci, Alessandro
Abstract : The biogeography and the ecology of the genus Turbinicarpus are scarcely known and the taxonomic segregation of the genus Rapicactus from Turbinicarpus has been debated. The present study aims to (i) evaluate the distribution of all taxa of Turbinicarpus in the full distributional range of the genus (NE Mexico); (ii) investigate the potential ecological divergence between Rapicactus and Turbinicarpus ; and (iii) analyse the influence of environmental variables on plant morphology. The distribution pattern of all taxa belonging to the genus Turbinicarpus s.l. ( Turbinicarpus + Rapicactus ) was mapped using information from 12 herbaria, as well as unpublished databases. The study area was divided into cells of 25 km × 25 km. The relationships between taxa richness, sampling effort and environmental variables were tested by using grid data, via spatially explicit models. The elevational distribution of populations and the effects of climate, latitude and elevation on the mean steam diameter of the populations were separately investigated for Turbinicarpus and Rapicactus . Turbinicarpus s.l. taxa richness is highest within 100°W and 101°W longitude, about 2500 km north of the equator, with maximum diversity in areas with a mean annual temperature of 17–19 °C and a mean annual rainfall of 550–650 mm. A significant relationship was observed between taxa richness and sampling effort, and between taxa richness and longitude, mean annual rainfall and calcium-rich substrate. Rapicactus taxa were found to grow at higher elevations compared with Turbinicarpus . Body size of the plants showed a negative relationship with latitude and elevation in Turbinicarpus, and a positive one with latitude in Rapicactus . The results showed that the genus Turbinicarpus s.l. presents diversity hotspots in the floristic regions of Chihuahuan Desert and Sierra Madre Oriental. The responses of Rapicactus and Turbinicarpus to latitudinal and elevational gradients were different, supporting the segregation of Rapicactus from Turbinicarpus .